Kerangka landasan pembinaan dan pengembangan industri kecil Kabupaten Gowa dalam Pelita IV (Kantor Departemen Perindustrian Kabupaten Gowa, 1984)
Program for the development of small-scale industreis for the fourth Five Year Development Plan in Kabupaten Gowa.